Nights in Rodanthe - Sparks, Nicholas (New York : Warner Books, Inc., 2002)
After her husband leaves her for a younger woman, forty-five-year-old Adrienne Willis reconsiders her entire life, until a trip to Rodanthe in North Carolina's outer banks leads to an encounter with successful surgeon Paul Flanner.
Keywords: DIVORCED PEOPLE